2016
DOI: 10.1016/j.bbi.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers are associated with decreased psychomotor speed in patients with major depressive disorder

Abstract: Previous data have demonstrated that administration of inflammatory cytokines or their inducers leads to altered basal ganglia function associated with reduced psychomotor speed. Decreased psychomotor speed, referred to clinically as psychomotor retardation, is a cardinal symptom of major depressive disorder (MDD) and has been associated with poor antidepressant treatment response. We therefore examined the association between plasma inflammatory markers and psychomotor speed in ninety-three un-medicated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
73
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 74 publications
12
73
3
Order By: Relevance
“…For example, in patients from a high-risk urban setting with a history of trauma, those who carried a CRP genotype (rs1130864) that is associated with elevated CRP concentrations had higher rates of posttraumatic stress disorder and reported higher scores for the loss of interest in activities (Michopoulos et al, 2015). Furthermore, recent data indicate that increased plasma concentrations of CRP and inflammatory cytokines and their soluble receptors correlate with symptoms of both anhedonia and psychomotor slowing in medically stable patients with MDD Goldsmith et al, 2016a;Haroon et al, 2016). These findings provide encouraging data that increased inflammation may be associated with symptoms of motivation and motor behavior across disorders, and may be useful for identifying subtypes of patients with psychiatric illness.…”
Section: Inflammation-induced Impairments In Motivation and Motor Actmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in patients from a high-risk urban setting with a history of trauma, those who carried a CRP genotype (rs1130864) that is associated with elevated CRP concentrations had higher rates of posttraumatic stress disorder and reported higher scores for the loss of interest in activities (Michopoulos et al, 2015). Furthermore, recent data indicate that increased plasma concentrations of CRP and inflammatory cytokines and their soluble receptors correlate with symptoms of both anhedonia and psychomotor slowing in medically stable patients with MDD Goldsmith et al, 2016a;Haroon et al, 2016). These findings provide encouraging data that increased inflammation may be associated with symptoms of motivation and motor behavior across disorders, and may be useful for identifying subtypes of patients with psychiatric illness.…”
Section: Inflammation-induced Impairments In Motivation and Motor Actmentioning
confidence: 99%
“…Furthermore, studies involving administration of inflammatory stimuli have informed recent work in patients with MDD, which has revealed similar relationships between increased peripheral cytokines and other inflammatory markers, alterations in DA-relevant neurocircuitry, motivational deficits, and psychomotor slowing Goldsmith et al, 2016a). Although many aspects of reward-related behaviors, such as reinforcement learning, have only begun to be explored in relation to increased inflammation, these concepts may be relevant to future studies examining relationships between DA and motivated behavior in the context of increased inflammation, and are reviewed in the context of health and psychiatric illness.…”
Section: Introductionmentioning
confidence: 99%
“…The association between levels of IL-6 and cognitive impairment in MDD has been investigated in the majority of studies addressing the impact of peripheral cytokines on cognition (Dannehl et al, 2014;Duivis et al, 2013;Elderkin-Thompson et al, 2012;Gimeno et al, 2008;Goldsmith et al, 2016a;Gorska-Ciebiada et al, 2015;Grassi-Oliveira et al, 2011;Jehn et al, 2015;Krogh et al, 2014;Matsushima et al, 2015). In these studies higher levels of IL-6 were associated with worse cognitive performance on encoding and recall in depressed and healthy elders (Elderkin-Thompson et al, 2012), psychomotor speed in medication-naïve patients with MDD (Goldsmith et al, 2016a) as well as immediate and delayed verbal recall in patients with MDD (Grassi-Oliveira et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is possible that cytokines are able to activate microglial cells leading to a dysfunctional synaptic pruning and consequent disturb in mood circuits 3 . Also, proinflammatory cytokines have been related to psychomotor retardation in depressed patients 8 ; an association that could be mediated by a possible effect of inflammation in the cortical striatal circuit 9 . Early data have shown an association of treatment resistant depression with increased levels of IL-6 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of IL-6 in depression is enhanced by data showing that increased IL-6 levels has been associated with psychomotor function such as decreased performance on simple and choice movement time tasks 29 . Supporting that high levels of IL-6 denotes a pro-inflammatory state that is associated with low responsiveness to SSRI, O'Brien et al 30 found that IL-6 levels (not measured in the baseline) were higher in resistant to SSRI treatment depressed patients in comparison to healthy individuals, while those with history of resistance to treatment but currently in remission did not differ from the healthy controls.…”
mentioning
confidence: 99%